2014
DOI: 10.1108/jap-03-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Experience of family caregivers of community-dwelling stroke survivors and risk of elder abuse: a qualitative study

Abstract: Purpose -The purpose of this paper is to explore the following questions. First, what are the experiences of family caregivers in caring for community-dwelling stroke survivors? Second, what services help or do not help the caregivers in managing their caregiving role? Design/methodology/approach -A qualitative study was conducted with a total of six focus group interviews with 29 stroke caregivers selected using convenience sampling in a local community centre. All interviews were recorded and transcribed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 43 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…Almost all studies reported the data collection process. Thirty studies provided the rationale for their research design, 9, 11, 23, 2527, 29, 3133, 35, 39, 41, 42, 4450, 5254, 58, 62, 65, 66, 70, 71 nine discussed the relationship between researcher and participants, 29, 42, 44, 46, 50, 54, 66, 70, 71 37 reported rigorous data analyses procedures, 4, 7, 9, 11, 24, 2628, 3037, 39, 4146, 4850, 5254, 58, 60, 63, 65, 6770 45 reported the ethical considerations, 4, 7, 9, 2325, 2729, 31, 32, 34, 3650, 5260, 6266, 6871 and 49 reported the recruitment strategy. 7, 9, 11, 2325, 2732, 3463, 6571 Of the 10 quantitative studies appraised using CEBMa, all clearly addressed the research question, methods, selection of participants, and had a sample representing the population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all studies reported the data collection process. Thirty studies provided the rationale for their research design, 9, 11, 23, 2527, 29, 3133, 35, 39, 41, 42, 4450, 5254, 58, 62, 65, 66, 70, 71 nine discussed the relationship between researcher and participants, 29, 42, 44, 46, 50, 54, 66, 70, 71 37 reported rigorous data analyses procedures, 4, 7, 9, 11, 24, 2628, 3037, 39, 4146, 4850, 5254, 58, 60, 63, 65, 6770 45 reported the ethical considerations, 4, 7, 9, 2325, 2729, 31, 32, 34, 3650, 5260, 6266, 6871 and 49 reported the recruitment strategy. 7, 9, 11, 2325, 2732, 3463, 6571 Of the 10 quantitative studies appraised using CEBMa, all clearly addressed the research question, methods, selection of participants, and had a sample representing the population.…”
Section: Resultsmentioning
confidence: 99%
“…anger and agitation 30, 59, 65, 69 , anxiety, 47, 81 and changes in behavior 23, 40, 70 – “He is more irritable because he realizes his limitations.” 65 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with 90 % of older Chinese living at home [11], much of the caregiving responsibilities are likely to fall on their family members. Although the Confucian value of filial piety may buffer the demands of caregiving, Chinese family caregivers are not exempt from caregiver stress [12]. Therefore, these caregivers, similar to their Western counterparts, are in need of effective, achievable, and acceptable interventions to help them manage caregiver stress.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study protocol, we detail a self-administered acupressure intervention protocol for Chinese family caregivers with caregiver stress based on our previous study on: (i) a similar model of self-administered acupressure previously tested in women with osteoarthritic knee pain that was shown to be feasible and safe [14]; (ii) factors aggravating or buffering caregiver stress among Chinese family caregivers [12]; (iii) a case management approach to improve the health outcomes of Chinese family caregivers of dementia patients [24]; and (iv) the scientific basis of symptom management [25]. In light of the needs of these caregivers and the little evidence on the effectiveness of self-administered acupressure in symptom management, a specifically designed self-administered acupressure intervention for Chinese family caregivers will be implemented and evaluated in this study.…”
Section: Introductionmentioning
confidence: 99%